The effectiveness of journals as arbiters of scientific impact - Paine, C. E. Timothy (Ecol Evol, 2018)
Academic publishers purport to be arbiters of knowledge, aiming to publish studies that advance the frontiers of their research domain. Yet the effectiveness of journal editors at identifying novel and important research is generally unknown, in part because of the confidential nature of the editorial and peer review process. Using questionnaires, we evaluated the degree to which journals are effective arbiters of scientific impact on the domain of Ecology, quantified by three key criteria. First, journals discriminated against low‐impact manuscripts: The probability of rejection increased as the number of citations gained by the published paper decreased. Second, journals were more likely to publish high‐impact manuscripts (those that obtained citations in 90th percentile for their journal) than run‐of‐the‐mill manuscripts; editors were only 23% and 41% as likely to reject an eventual high‐impact paper (pre‐ versus postreview rejection) compared to a run‐of‐the‐mill paper. Third, editors did occasionally reject papers that went on to be highly cited. Error rates were low, however: Only 3.8% of rejected papers gained more citations than the median article in the journal that rejected them, and only 9.2% of rejected manuscripts went on to be high‐impact papers in the (generally lower impact factor) publishing journal. The effectiveness of scientific arbitration increased with journal prominence, although some highly prominent journals were no more effective than much less prominent ones. We conclude that the academic publishing system, founded on peer review, appropriately recognizes the significance of research contained in manuscripts, as measured by the number of citations that manuscripts obtain after publication, even though some errors are made. We therefore recommend that authors reduce publication delays by choosing journals appropriate to the significance of their research.